2016
DOI: 10.1002/hon.2331
|View full text |Cite
|
Sign up to set email alerts
|

Independent prognostic impact of CD15 on complete remission achievement in patients with acute myeloid leukemia

Abstract: The prognostic role of CD15 in acute myeloid leukemia (AML) has been tested in different studies with conflicting results. To address this issue, we retrospectively evaluated a cohort of 460 AML patients of all ages with the exclusion of acute promyelocytic leukemia (M/F 243/217, median age 50.6 years [range 0.9-81.2]) intensively treated at our institute between January 1999 and December 2010. CD15 positivity was found in 171 of 406 evaluable patients (42.1%). Complete remission (CR) was achieved by 334 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…published a large retrospective analysis of 460 AML patients—173 being positive for CD15—and demonstrated CD15 to be of independent prognostic value for CR achievement. Those patients tend to have a superior survival rate, although this analysis missed statistical significance [21]. This rather favorable impact on AML is in contrast to our results indicating poor survival and poor response of AML with blast vacuolization to standard induction chemotherapy.…”
Section: Discussioncontrasting
confidence: 78%
“…published a large retrospective analysis of 460 AML patients—173 being positive for CD15—and demonstrated CD15 to be of independent prognostic value for CR achievement. Those patients tend to have a superior survival rate, although this analysis missed statistical significance [21]. This rather favorable impact on AML is in contrast to our results indicating poor survival and poor response of AML with blast vacuolization to standard induction chemotherapy.…”
Section: Discussioncontrasting
confidence: 78%
“…The CD15 antigen, a member of the cell adhesion molecule family, is normally expressed on neutrophils. 27 Previous studies have shown that CD15 expression was associated with a high CR rate [28][29][30] and long OS duration. 31 Repp et al reported that CD33 expression was associated with long OS.…”
Section: Discussionmentioning
confidence: 98%
“…Although increasing findings have improved understanding of the pathogenesis of AML, standard therapies have not changed for over 30 years. With the recent development of targeted and immunotherapy, a number of ongoing studies aim to produce novel AML therapies, including conventional cytotoxic chemotherapies, genetic and epigenetic targeted therapies, and immunotherapies [3][4][5][6]. The T cell immune status of patients is an important factor related to the prognosis of leukemia [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%